Catalytic Degradation of Anionic Organic Dye on Greenly Synthesized CuO/ZnO Nanocomposites - Enshirah Da’na; Amel Taha; Manal Hessien (Applied Sciences, 2022)
CuO/ZnO nanocomposites were greenly prepared and tested for the catalytic degradation of methyl orange. The XRD analysis confirmed the existence of CuO and ZnO with crystallite sizes within the range of 15–30 nm. TEM and SEM images showed different morphological properties. The TGA analysis revealed a good thermal stability of the nanocomposite, with a total loss of less than 18% at a temperature of 700 °C. The nanocomposites were tested for the catalytic degradation of methyl orange under mild conditions with a catalyst mass/wastewater volume of 10 g/3 L, an initial dye concentration of 40 ppm, a pH of 4.5, and a degradation time of 3 h. The best efficiency of 49.1% was achieved by CuO nanoparticles (C), followed by 47.6%, which was obtained by 1C1Z. The degradation efficiency of ZnO (Z) was 16.4%, and it was increased by increasing the CuO precursor in the synthesis mixture, while adding ZnO to the CuO, resulting in a decrease in its catalytic performance.